2021
DOI: 10.1021/acsnano.1c06016
|View full text |Cite
|
Sign up to set email alerts
|

Photoluminescence Switching Effect in a Two-Dimensional Atomic Crystal

Abstract: Two-dimensional materials are an emerging class of materials with a wide range of electrical and optical properties and potential applications. Single-layer structures of semiconducting transition metal dichalcogenides are gaining increasing attention for use in field-effect transistors. Here, we report a photoluminescence switching effect based on single-layer WSe 2 transistors. Dual gates are used to tune the photoluminescence intensity. In particular, a side-gate is utilized to control the location of ions … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 40 publications
0
8
0
Order By: Relevance
“…Several recent applications of electrolyte gating have demonstrated that the excitonic spectrum, one of the most prominent features of 2D semiconductors, can be efficiently tuned by electrolyte-gated doping. Similarly, very detailed studies of the Raman spectra of TMDCs, summarized in Figure , demonstrated that while the in-plane vibrational mode (E 2g 1 ) is insensitive to doping, the out-of-plane vibrational mode (A 1g ) is highly tunable by electron (but not hole) doping. , Advances in electrolyte gating at ultramicroelectrodes enabled simultaneous electron tunneling across hexagonal boron nitride and measurement of a redox reaction rate to be realized . This study revealed unproven predictions from the Marcus–Hush theory of electron transfer, such as the limiting current plateauing, and provided a platform to study complex reaction mechanisms.…”
Section: Electrolyte Gating Of 2d Materialsmentioning
confidence: 99%
See 1 more Smart Citation
“…Several recent applications of electrolyte gating have demonstrated that the excitonic spectrum, one of the most prominent features of 2D semiconductors, can be efficiently tuned by electrolyte-gated doping. Similarly, very detailed studies of the Raman spectra of TMDCs, summarized in Figure , demonstrated that while the in-plane vibrational mode (E 2g 1 ) is insensitive to doping, the out-of-plane vibrational mode (A 1g ) is highly tunable by electron (but not hole) doping. , Advances in electrolyte gating at ultramicroelectrodes enabled simultaneous electron tunneling across hexagonal boron nitride and measurement of a redox reaction rate to be realized . This study revealed unproven predictions from the Marcus–Hush theory of electron transfer, such as the limiting current plateauing, and provided a platform to study complex reaction mechanisms.…”
Section: Electrolyte Gating Of 2d Materialsmentioning
confidence: 99%
“…The robustness of the electrolyte gate and the insensitivity of its performance to the geometric configuration also facilitates in situ evaluation of the optical properties upon the applied voltage. These advantages have been utilized to achieve photoluminescence switching in monolayer WSe 2 , with on–off ratios considerably larger than those for a single gate, and to demonstrate the potential for integrating electrolyte gating in optoelectronic circuits …”
Section: Dual Gating Of 2d Materialsmentioning
confidence: 99%
“…This gating mechanism induces high sheet carrier densities (10 13 –10 14 cm –2 ) in various organic and inorganic semiconductors. , EDL gating is also used in fundamental research of low-dimensional materials. For example, this technique has been effective in controlling light scattering and emission, , surface plasmon resonance, ,, and the transition temperature for superconductivity ,, in layered materials including graphene, 2D metals, and transition-metal dichalcogenides (TMDs).…”
Section: Introductionmentioning
confidence: 99%
“…PLs, are quenched. , In WSe 2 -based vdW heterostructures, the PLs exhibit varied characteristics by stacking with different materials, by applying gate voltages, , or by introducing chemical doping. , But the tunability of the optical signals is poor: e.g., the PL on/off ratio was only ∼11 . Even though dual gates were applied on the WSe 2 , the ratio is slightly increased to 90 . Furthermore, in such a structural configuration, electrical signals are inaccessible.…”
mentioning
confidence: 99%
“…PLs, are quenched. 22,23 In WSe materials, 24−26 by applying gate voltages, 27,28 or by introducing chemical doping. 29,30 But the tunability of the optical signals is poor: e.g., the PL on/off ratio was only ∼11.…”
mentioning
confidence: 99%